Ornithophily - Ibrahim, Faridah Hanum; Ibrahim, Siti Aminah (Universiti Putra Malaysia Press, 2015)
Pollination is a process where pollen grains are transferred from the stamens (male part) to the stigma (female part) of the flower; if it happens on the same plant it is called self pollination or if on another plant of the same species it is termed cross pollination. Pollination, however, is an accidental process that happens when animals such as bees, flies, wasps, moths, butterflies, bats, ants, beetles, and birds forage for food such as pollen and nectar from the flower. It also happens when the wind blows the pollen to the stigma of flowers. Wind pollinated flower are usually dull, small, without petals, and unscented. On the other hand, those flowers pollinated by animals are usually brightly-coloured and attractive, has a good amount of nectar or has a strong scent which can be sweet or foul smelling.